Priapism associated with lumbar stenosis: case report and literature review - Nichols, Noah Michael Linwood (J Spine Surg, 2019)
Lumbar spinal stenosis (LSS) is characterized by narrowing of the central canal, lateral recesses, or foramina leading to compression of neural tissue. The clinical syndrome associated with LSS is usually neurogenic claudication, which often presents as lower back and extremity pain, numbness, and tingling upon ambulation. Autonomic dysfunction is rarely observed in patients with LSS; however, a subset of male patients has been reported to experience intermittent priapism associated with the onset of neurogenic claudication symptoms. We present the case of a 33-year-old male who was diagnosed with LSS associated with neurogenic claudication and priapism who underwent minimally invasive decompressive surgery. Complete resolution of claudication and priapism was observed at the 6-week follow-up visit. This case report highlights minimally invasive lumbar decompression as an effective treatment for the rarely observed presentation of priapism associated with LSS.